Geldanlagemotive von Student*innen der IU Internationale Hochschule in Zeiten der Krise - Julia Pitters; Susanne Theresia Weber (IU Internationale Hochschule, 2025)
– The IU Compass Project titled "Geldanlagemotive von Student*innen der IU Internationale Hochschule in Zeiten der Krise" investigates the driving forces behind the financial decision-making and personal investment behaviors of students at IU Internationale Hochschule. This research addresses both tangible and intangible factors influencing the decision to invest in personal development, such as the pursuit of higher education. Students' investment preferences are shaped by a combination of personal attributes and current developments in the financial markets and geopolitics. A central aspect of this study is the examination of the financial literacy of aspiring academics. Key questions addressed include students' risk assessments of various investment forms, the perceived threat of crises like the Ukraine war and inflation, and the role of demographic factors in financial decisions. The results indicate significant gender differences in risk attitudes and a strong need for improved financial competence. The study aims to provide fundamental insights into the relevance of financial education for IU students and advocates for curricular enhancements to support informed financial decision-making processes.
Keywords: 650; Generation Z; Financial behavior; Wealth accumulation; Investment; Students; Financial education